External Interventions and Consequences in the Horn of Africa - Bereketeab, Redie (The Journal of US-Africa Studies, 2021)
This paper examines external interventions, subsequent configurations of alliances and consequences in the Horn of Africa (HOA). The HOA, major part of its political history is shaped and reshaped by external interventions and constant shifts of alliances and political configurations. Colonialism, Cold War, war on terror, piracy and scramble for resources have all shaped the politics of the region. Superpower rivalry during Cold War left its interminable print in the region. The GCC crisis and the Yemen war induced greater involvement of those states in the region. Its crucial strategic location makes the region highly coveted by external actors making it an easy prey for external power struggle. This renders the region the most conflicted in the African continent. Recently, the region has witnessed convergence of military forces of major global powers. This in turn sparks reactions of radicalism, fundamentalism and extremism. The paper argues the conflated interventions and constant shifts of alliances generate convolute pathologies that plague the HOA. Keywords: Horn of Africa, external interventions, alliances, consequences